Flavonoids of Rosa roxburghii Tratt Exhibit Anti‐Apoptosis Properties by Regulating PARP‐1/AIF. Issue 11 (25th May 2017) - Xu, Ping; Liu, Xingxia; Xiong, Xiwen; Zhang, Wenbo; Cai, Xinhua; Qiu, Peiyong; Hao, Minghua; Wang, Lijuan; Lu, Dandan; Zhang, Xiuhua; Yang, Wancai
ABSTRACT: Radioprotection is an important approach to reduce the side‐effects of radiotherapy. The radioprotective effect of the flavonoids of Rosa roxburghii Tratt (FRT) has been confirmed, and the mechanism has been identified as theBcl‐2/caspase‐3/PARP‐1 signaling pathway. In this study, we investigated the effects of FRT on the intercellular adhesion molecule (ICAM), and vascular cell adhesion protein (VCAM) in addition to apoptosis‐related proteins such as Bax/Bcl‐2, p‐ERK/ERK, p‐p53/p53, and p‐p38/p38. In the present study, we focused on the effect of FRT on PARP‐1/AIF. Ionizing radiation triggered the activation of PARP‐1 and AIF translocation from the mitochondrion to the nucleus. The inhibition of PARP‐1/AIF signaling pathway by FRT was investigated. Our results showed that the expressions of Bax/Bcl‐2, p‐ERK/ ERK, p‐p53/p53, and p‐p38/p38 were decreased after FRT treatment compared with the radiation‐treated group. FRT inhibited PARP‐1 activation to inhibit AIF translocation from mitochondrion to nucleus. Pretreatment with FRT diminished the comet's tail and reduced fragments in six Gy‐irradiated thymocytes compared with the irradiated cells without FRT treatment. We conclude that FRT enhanced radioprotection at least partially by regulating PARP‐1/AIF to reduce apoptosis. J. Cell. Biochem. 118: 3943–3952, 2017. © 2017 Wiley Periodicals, Inc. Abstract : (1) Ionizing radiation triggered activiation of PARP‐1 and AIF translocation from mitochondrion to nucleus. (2) inhibition of PARP‐1/AIF signal pathway by FRT was investigated. (3) Our results showed that FRT regulated apoptosis related proteins in addition to VCAM and it inhibited PARP‐1 activiation to inhibit AIF translocation from mitochondrion to nucleus.